Dynamic association between socio-economic, environmental and logistic operations: Evidence from SSA BRI host countries - Ali Aden, Waiss; Zheng, Jianfeng; Almoshageh, Meshal; Ullah, Irfan; Aziz, Qaiser; Jamal, Arshad (Frontiers in Environmental Science, 2022)
Eco-logistics, usually known as green logistics, refers to a set of sustainable policies and initiatives targeted at lowering the environmental impact of this business's activities. This logistics concept influences the design of procedures, structures, systems, and equipment used in the transportation, distribution, and storage of commodities. The traditional approach to logistics frequently leaves environmental sustainability on the wayside when making decisions. Green logistics, on the other hand, seeks to strike a balance between ecological and economy. The Belt and Road Initiative (BRI) is mostly dependent on conventional, undeveloped logistic trade routes, such as the land based and ocean Silk Road. Poor logistical infrastructure throughout the BRI region limits trade opportunities and economic development and also leads a several of social and environmental issues. Consequently, this study examines the connection among green logistic operations, country-level economic, environmental, and social indices, as well as the BRI. Three important findings have been made through the application of the generalized method of moments (GMM) and system generalized method of moments (Sys-GMM) estimation approaches in this research. To begin, Chinese outbound direct investment in other countries' economies leads to considerable improvements in the quality and quantity of green logistic operations in transportation infrastructure, cost, time, customs services, tracking, and the consistency of international shipments. Second, improved infrastructure for transportation, faster customs processing, and competent logistics services considerably reduce carbon emissions as a result of supply chain energy efficiency. Additionally, using renewable energy sources greatly raises the standard of logistics operations. These findings show that more effective infrastructure is provided by green logistic operations, and supply chain partners share information more frequently, increasing trade volume, growth potential, and environmental sustainability. Finally, improved logistical efficiency attributable to increased institutional quality reduces social concerns.